The global village revisited : art, politics, and television talk shows - Dixon, Kathleen, 1955- (Lexington Books, 2009)
In The Global Village Re-visited: Art, Politics, and Television Talk Shows, Kathleen Dixon explores three case studies from Belgium, Bulgaria, and the United States, and reveals how these cases interanimate to produces a new view of the talk show as a global phenomenon, and as a negotiation among the forces of late capitalism, the unnamed but still palpable audience, and the individual rhetors, artists, and technicians who make the shows.